Progressive cerebellar atrophy in a patient with complex II and III deficiency and a novel deleterious variant in SDHA: A Counseling Conundrum. Issue 6 (7th May 2021) - Sturrock, Beattie R. H.; Macnamara, Ellen F.; McGuire, Peter; Kruk, Shannon; Yang, Ivan; Murphy, Jennifer; ,; Tifft, Cyndi J.; Gordon‐Lipkin, Eliza
Abstract: Background: Complex II is an essential component of the electron transport chain, linking it with the tricarboxylic acid cycle. Its four subunits are encoded in the nuclear genome, and deleterious variants in these genes, including SDHA (OMIM 600857), are associated with a wide range of symptoms including neurological disease, cardiomyopathy, and neoplasia (paraganglioma‐pheochromocytomas (PGL/PCC), and gastrointestinal stromal tumors). Deleterious variants of SDHA are most frequently associated with Leigh and Leigh‐like syndromes. Methods and Results: Here, we describe a case of a 9‐year‐old boy with tremor, nystagmus, hypotonia, developmental delay, significant ataxia, and progressive cerebellar atrophy. He was found to have biallelic variants in SDHA, a known pathogenic variant (c.91C>T (p.R31*)), and a variant of unknown significance (c.454G>A (p.E152K)). Deficient activity of complexes II and III was detected in fibroblasts from the patient consistent with a diagnosis of a respiratory chain disorder. Conclusion: We, therefore, consider whether c.454G>A (p.E152K) is, indeed, a pathogenic variant, and what implications it has for family members who carry the same variant. Abstract : Progressive cerebellar atrophy in a patient with complexes II and III deficiency and SDHA compound heterozygous variants. These variants were considered pathogenic, given respiratory chain findings, and the family was counseled based on the presence of pathogenic variants.